Molecular clumps disguising their star formation efficiency per free-fall time: what we can do not to be fooled - Parmentier, Geneviève (The astrophysical journal, 2020)
The presence of a volume-density gradient in molecular clumps allows them to raise their star formation rate compared with what they would experience if their gas were uniform in density. This higher value for the star formation rate yields in turn a higher star formation efficiency per free-fall time that we measure. The measured star formation efficiency per free-fall time, , of clumps is therefore plagued by a degeneracy, as two factors contribute to it: one is the density gradient of the clump gas, the other is the intrinsic star formation efficiency per free-fall time, , with which the clump would form stars should there be no gas-density gradient. This paper presents a method allowing one to recover the intrinsic efficiency of a centrally concentrated clump. It hinges on the relation between the surface densities in stars and gas measured locally from clump center to clump edge. Knowledge of the initial density profile of the clump gas is not required. A step-by-step description of the method is provided as a tool in hand for observers. Once has been estimated, it can be compared with its measured, clump-averaged, counterpart, , to quantify the impact that the initial gas-density profile of a clump has had on its star formation history.
Gesehen am 07.05.2020